Elevated De Ritis Ratio Is Associated With Poor Prognosis in COVID-19: A Systematic Review and Meta-Analysis - Pranata, Raymond; Huang, Ian; Lim, Michael Anthonius; Yonas, Emir; Vania, Rachel; Lukito, Antonia Anna; Nasution, Sally Aman; Siswanto, Bambang Budi; Kuswardhani, Raden A. Tuty (Frontiers in Medicine, 2021)
Objective This meta-analysis aims to assess whether elevated De Ritis ratio is associated with poor prognosis in patients with coronavirus 2019 (COVID-19). Methods A systematic literature search was performed using PubMed, Embase, and EuropePMC up until 17th September 2021. De Ritis ratio is also known as AST/ALT ratio. The main outcome was poor prognosis, a composite of mortality, severity, the need for ICU care and intubation. The effect measure was odds ratios (ORs) and mean differences. We generate sensitivity and specificity; negative and positive likelihood ratio (NLR and PLR), diagnostic odds ratio (DOR), and area under curve (AUC). Results There were eight studies with 4606 patients. De Ritis ratio was elevated in 44% of the patients. Patients with poor prognosis have higher De Ritis ratio (mean difference 0.41 [0.31, 0.50], p<0.001; I2: 81.0%) and subgroup analysis showed that non-survivors also have higher De Ritis Ratio (mean difference 0.47 [0.46, 0.48], p<0.001; I2: 0%). Elevated De Ritis ratio was associated with poor prognosis (OR 3.28 [2.39, 4.52], p<0.001; I2: 35.8%). It has a sensitivity of 55% (36-73), specificity of 71% (52-85), PLR 1.9, NLR 0.63, DOR of 3 (2-4), and AUC of 0.67 (0.63-0.71). The posterior probability of poor prognosis was 38% if De Ritis was elevated, and 17% if De Ritis was not elevated. Conclusion Elevated De Ritis ratio is associated with poor prognosis in patients with COVID-19. PROSPERO ID: CRD42020216634